(untitled) (Proceedings of the International Conference on Sustainable Management for Peace and Harmony, 2025)
In this era of global development, the business sector faces increasingly dynamic and intense competition. Companies are required not only to offer quality products but also to create meaningful interactions that differentiate them from competitors. To win customer preferences and retain existing consumers, marketers must continuously innovate and develop strategies that form strong emotional bonds through positive customer experiences. One effective approach to achieve this is Experiential Marketing, which aims to touch customer emotions and provide memorable experiences, thereby increasing satisfaction and loyalty. This study aims to determine the effect of Experiential Marketing on revisit intention among Alfamart customers in Kupang City. The research employs a quantitative associative method, with data collected through an online questionnaire involving 96 respondents (n=96), selected using a non-probability sampling technique. The Experiential Marketing variable is measured through five key dimensions: Sense (sensory experiences), Feel (emotional engagement), Think (cognitive stimulation), Act (behavioral influence), and Relate (social identity and connection). The results of simple linear regression analysis indicate that Experiential Marketing has a significant and positive effect on revisit intention, contributing 55.1% to the variation in revisit behavior. The remaining 44.9% is influenced by other factors not covered in this study, such as brand trust, service quality, and price perception. Enhancing the five experiential dimensions can encourage repeat visits, increase transaction frequency, and raise the average purchase value per visit. For store managers, this means designing in-store experiences that stimulate the senses, evoke positive emotions, engage customers cognitively, encourage active participation, and foster social connections among shoppers. For investors, the 55.1% contribution reflects a high potential for customer loyalty, reduced acquisition costs, and more predictable revenue streams. Ultimately, such strategies not only enhance short-term sales performance but also support long-term business sustainability and competitive advantage.